Wind Energy Conversion Based on Matrix Converter - Mutharasan Anburaj; Rameshkumar T; Ajitha A (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
In recent years renewable sources such as solar, wave and wind are used for the generation of electricity. Wind is one of the major renewable sources. The amount of energy from a Wind Energy Conversion System (WECS) depends not only on the wind at the site, but also on the control strategy used for the WECS. In assistance to get the appropriate wind energy from the conversion system, wind turbine generator will be run in variable speed mode. The variable speed capability is achieved through the use of an advanced power electronic converter. Fixed speed wind turbines and induction generators are often used in wind farms. But the limitations of such generators are low efficiency and poor power quality which necessitates the variable speed wind turbine generators such as Doubly Fed Induction Generator (DFIG) and Permanent Magnet Synchronous Generator (PMSG). A high-performance configuration can be obtained by using Scherbius drive composed of a DFIG and a converter in combination AC-DC-AC connect between stator & rotor points for providing the required variable speed operation.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6025